The Mabinogi and Other Medieval Welsh Tales - Ford, Patrick K. (University of California Press, 2019)
The four stories that make up the Mabinogi, along with three additional tales from the same tradition, form this collection and compose the core of the ancient Welsh mythological cycle. Included are only those stories that have remained unadulterated by the influence of the French Arthurian romances, providing a rare, authentic selection of the finest works in medieval Celtic literature. This landmark edition translated by Patrick K. Ford is a literary achievement of the highest order